2021
DOI: 10.1136/bmjresp-2020-000813
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of adult patients admitted with COVID-19 in East London: a retrospective cohort analysis

Abstract: BackgroundDescriptions of clinical characteristics of patients hospitalised withCOVID-19, their clinical course and short-term inpatient and outpatient outcomes in deprived urban populations in the UK are still relatively sparse. We describe the epidemiology, clinical course, experience of non-invasive ventilation and intensive care, mortality and short-term sequelae of patients admitted to two large District General Hospitals across a large East London National Health Service Trust during the first wave of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
5
14
0
1
Order By: Relevance
“…Abate et al (2021) conducted a systematic review and found a 48% prevalence of comorbidities in hospitalized patients, with diabetes mellitus (48%) predominating, followed by hypertension and cardiovascular diseases (15%) [ 38 ]. Among the main risk factors listed in this study were chronic cardiovascular disease, diabetes mellitus and obesity, which have also been found in other studies [ 39 , 40 , 41 , 42 ]. Our findings indicated the presence of a risk factor in 73% of deaths, but these results can be explained by the fact that we only examined the number of deaths.…”
Section: Discussionsupporting
confidence: 87%
“…Abate et al (2021) conducted a systematic review and found a 48% prevalence of comorbidities in hospitalized patients, with diabetes mellitus (48%) predominating, followed by hypertension and cardiovascular diseases (15%) [ 38 ]. Among the main risk factors listed in this study were chronic cardiovascular disease, diabetes mellitus and obesity, which have also been found in other studies [ 39 , 40 , 41 , 42 ]. Our findings indicated the presence of a risk factor in 73% of deaths, but these results can be explained by the fact that we only examined the number of deaths.…”
Section: Discussionsupporting
confidence: 87%
“…The average AXIS score for all included studies was 16.9 (±2.0) out of a possible 20, which may indicate a moderate risk of bias. The major sources of bias were the use of the convenience sampling methods, which was utilised by 38 of the 39 studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], and possible non-response bias in 12 studies [16,17,[25][26][27]32,[34][35][36][37][38][39]48]. The results of the AXIS critical appraisal for each included study are displayed in Table 3.…”
Section: Quality Appraisal and Risk Of Biasmentioning
confidence: 99%
“…The idea that SARS-CoV-2 infection could be associated with long-term health outcomes first appeared in the literature in mid-2020 [11], along with previous evidence of longhaul symptoms following the Ebola [12] virus outbreak and infections from previous coronaviruses [13,14]. COVID-19 survivors have been shown to experience a constellation of symptoms such as fatigue, dyspnea or breathlessness [8,15], palpitations [16,17], brain fog, lack of concentration [18,19], sleep disturbances (i.e., insomnia) [20], headache [17,[21][22][23][24][25], orthostatic intolerance [25], anxiety and post-traumatic stress disorder [20,23,[26][27][28], chest pain, joint pain [8], sore throat [17], and hair loss [15] persisting >4 weeks after recovery. These clinical sequelae share similarities with post-acute symptoms reported after severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) epidemics, caused by previous coronaviruses [14].…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 99%
“…Data from a large retrospective cohort study in the UK showed that patients admitted to the hospital for COVID-19 were more frequently male [79]. Males also showed higher mortality [15]. Conversely, COVID-19-related multi-organ dysfunction occurred in a gender-neutral fashion, with both male and female COVID-19 survivors showing a similar risk of respiratory and CV complications [79].…”
Section: Is Pasc Gender-specific?mentioning
confidence: 99%